Distribution and predictive factors of seizure types in 104 cases. (30th October 2013) - Lacombe, V. A.; Mayes, M.; Mosseri, S.; Reed, S. M.; Ou, T. H.
Summary Reasons for performing the study Although many studies have been performed to classify seizures by type in man and small animals, a similar study in horses is lacking. Objectives The aims of this study were as follows: 1) to characterise the distribution of seizure types in 104 horses presented for seizure disorders to a referral veterinary hospital; and 2) to characterise the various types of seizures by identifying associated clinical factors. Study design Retrospective analysis of clinical records. Methods Seizures were classified based on seizure type, according to the most recent accepted definitions in both human and small animal epileptology. History, clinical and neurological examinations, diagnostic investigations and post mortem examinations, when available, were recorded for univariable and multivariable logistic regression analyses. Results Seizures were categorised as primary generalised in 23% of horses, focal without secondary generalisation in 42% of cases and secondary generalised in 24% of cases. The type of seizure could not be classified in 11% of cases. Significant associations were found between seizure type and the following characteristics: 1) gender; 2) frequency of seizures; and 3) presence of seizures during hospitalisation. Seizure type was not significantly associated with aetiology. For a horse with recurrent seizures, the odds of having focal seizures was 3.7 times higher (P = 0.02) than in a similar horse with nonrecurring seizures in the final logistic regression model. Conclusions The majority of the seizures described were focal seizures with or without secondary generalisation. The clinical presentation was independent of the underlying disease.